Mundane diplomacies for the practice of European geopolitics. (June 2015) - Jones, Alun; Clark, Julian
Highlights: We offer a practice-based account of diplomacy. Diplomats are central to the production and transaction of geopolitical knowledge. There is a changing geography of diplomacy underway. We explore how practices can go awry in the move to integrative diplomacy. Abstract: This paper offers a practice-based account of diplomacy given that diplomats are central to the production and circulation of geopolitics. We contend that there is a changing geography of diplomacy underway from state-centred to "integrative diplomacy", prompting the need for reorganisation of the modalities that shape and regulate state presence. Such reorganisation brings with it the challenge of fashioning new pathways of diplomatic engagement to counter the disordering of routinized mundane diplomatic practices, alongside new possibilities for diplomatic space to be used by various actors and interests. In sum, the move to integrative diplomacy commands closer academic attention to the contemporary geographies of diplomatic practice, and how these practices are transacted in diverse spatial settings, sites and domains, under conditions of multiple contestation of state authority and legitimacy. Using extensive European empirical materials, we argue that the ways in which diplomats devise, trial, make claims and counter-claims about geopolitical representations are ripe for practice-based analysis. We do this through an exploration of diplomacy's geographical dimensions, that is, its everyday spaces and places, orderings and transactions and show how practices can go awry in the move to integrative diplomacy.